Resilience in Children: Developmental Perspectives - Ann S. Masten; Andrew J. Barnes (MDPI AG, 2018)
Advances in developmental resilience science are highlighted with commentary on implications for pediatric systems that aspire to promote healthy development over the life course. Resilience science is surging along with growing concerns about the consequences of adverse childhood experiences on lifelong development. Resilience is defined as the capacity of a system to adapt successfully to challenges that threaten the function, survival, or future development of the system. This definition is scalable across system levels and across disciplines, applicable to resilience in a person, a family, a health care system, a community, an economy, or other systems. Robust findings on resilience in childhood underscore the importance of exposure dose; fundamental adaptive systems embedded in the lives of individuals and their interactions with other systems; developmental timing; and the crucial role of healthcare practitioners and educators as well as family caregivers in nurturing resilience on the “front lines” of lived childhood experience. Resilience science suggests that human resilience is common, dynamic, generated through myriad interactions of multiple systems from the biological to the sociocultural, and mutable given strategic targeting and timing. Implications for pediatric practice and training are discussed.